Free-space continuous-variable quantum key distribution under high background noise - Xue-Tao Zheng; Qi-Fa Zhang; Jie Ling; Guang-Can Guo; Zheng-Fu Han (npj Quantum Information)
Abstract One of the difficulties in the application of quantum communication is the fragility of its encoded quantum states. Conventional quantum key distribution (QKD) requires strict filtering operations at the receiver. Any ambient light entering the system can significantly increase the bit error rate and even render the system inoperable. We present a continuous-variable quantum key distribution (CV-QKD) system that can function effectively during the day or even on rainy days without complex filtering operations. The Gaussian modulated coherent state continuous-variable quantum key distribution (GMCS CV-QKD) system demonstrates robustness, maintaining a secure key rate (SKR) of more than 100 kbps when operating at a frequency of 10 MHz, which lays the foundation for low-cost, highly robust free-space quantum communication.